Cerebral palsy in adult patients: constraint-induced movement therapy is effective to reverse the nonuse of the affected upper limb - Ana Cecília P. Oliveira; Camila de Freitas; Rafael Eras-Garcia; Gabriela S. Matuti; Juliana F. Santos; Clarissa B. Oliveira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To determine if the original protocol of Constraint-Induced Movement Therapy (CIMT), is adequate to reverse the nonuse of the affected upper limb (AUL) in patients with Cerebral Palsy (CP) in adulthood. Method The study included 10 patients diagnosed with CP hemiparesis had attended the adult protocol CIMT, from January/August 2009/2014. Results Average age 24.6 (SD 9.44); MAL average pretreatment How Often (HO) = 0.72 and How Well (HW) = 0.68 and post-treatment HO = 3.77 and HW = 3.60 (p ≤ 0.001) and pretreatment WMFT average = 21.03 and post-treatment average = 18.91 (p = 0.350). Conclusion The constraint-induced movement therapy is effective to reverse the nonuse learn of the AUL in adult patients with CP.